A Novel Ultra-Broadband and Low-Cost Termination Concept Based on a Dual-Layer SIW Topology - Birkenhauer, Christoph; Vossiek, Martin (2021 IEEE International Conference on Microwaves, Antennas, Communications and Electronic Systems (COMCAS), 2021)
In this work a novel concept to realize wideband matches at high frequencies with standard manufacturing processes without the need for additional fabrication steps or materials is presented. This is achieved by incorporating the high dielectric losses in substrates based on epoxy and glass fibers. The benefits of this approach for real applications are demonstrated by the design and fabrication of an illustrative load. This wideband match was then validated with an absolute reflection coefficient of around −20dB between 50 and 110GHz. Parameters critical for performance are presented and their impact is examined in theory and verified by full wave simulations and measurement
Keywords: substrate integrated waveguide; SIW; match; load; termination; V-band; E-band; W-band; millimeter-wave; mmW